How Pediatric Anesthesiologists Manage Children with OSA Undergoing Tonsillectomy. (January 2020) - Roberts, Christopher; Al Sayegh, Raihanah; Ellison, Pavithra Ranganathan; Sedeek, Khaled; Carr, Michele M.
Objective: The purpose of this study was to describe typical anesthesia practices for children with obstructive sleep apnea (OSA). Study Design: Online survey. Method: A sample of pediatric anesthesiologists received the survey by email. Results: 110 respondents were included. 46.4% worked in a free-standing children's hospital and 32.7% worked in a children's facility within a general hospital. 73.6% taught residents. 44.4% saw at least one child with OSA per week, 25.5% saw them daily. On a 100-mm visual analog scale, respondents rated their comfort with managing these children as 84.94 (SD 17.59). For children with severe OSA, 53.6% gave oral midazolam preoperatively, but 24.5% typically withheld premedication and had the parent present for induction. 68.2% would typically use nitrous oxide for inhalational induction. 68.2% used fentanyl intraoperatively, while 20.0% used morphine. 61.5% reduced their intraop narcotic dose for children with OSA. 98.2% used intraoperative dexamethasone, 58.2% used 0.5 mg/kg for the dose. 98.2% used ondansetron, 62.7% used IV acetaminophen, and 8.2% used IV NSAIDs. 83.6% extubated awake. 27.3% of respondents stated that their institution had standardized guidelines for perioperative management of children with OSA undergoing adenotonsillectomy. People who worked in children's hospitals, who had >10 years of experience, or who saw children with OSA frequently were significantly more comfortable dealing with children with OSA ( P < 0.05). Conclusion: Apart from using intraoperative dexamethasone and ondansetron, management varied. These children would likely benefit from best practices perioperative management guidelines.